The role of endoscopic injection sclerotheraphy in upper gastrointestinal bleeding due to peptic ulcers* - , Sedat ERTEM, Erhun KASIRGA, Ali Rıza SARUL, Zeynel Abidin ALTINAY (Turkish Journal of Gastroenterology 1, 2019)
-